Cooling of a plate with general boundary conditions - F. D. Zaman; R. Al-Khairy (International Journal of Mathematics and Mathematical Sciences)
We consider steady state temperature distribution in a homogeneous rectangular infinite plate the lower part of which is cooled by a fluid flowing at a constant velocity while the upper part satisfies the general mixed boundary conditions. The Wiener-Hopf method has been used to obtain the solution in the infinite series form and some special cases have been discussed.